Evaluation of the Efficacy of Systemic Inflammatory Markers in Predicting Medical Treatment Failure in Patients with Tubo-Ovarian Abscess - Akinci, Guzide Ece; Karacan, Tolga; Baykus, Yakup; Tigli, Alihan; Deniz, Rulin; Kilic, Suleyman Sirri; Aydin, Suleyman (Dove Medical Press Ltd, 2026)
Background/Objectives: Tubo-ovarian abscess (TOA), a serious complication of pelvic inflammatory disease, poses a serious risk to sexually active women, characterized by high rates of morbidity and mortality. Despite antibiotic therapy being the primary treatment for non-ruptured, stable TOA cases, failure rates of medical management remain as high as 30%. This study investigates the potential of systemic inflammatory markers, particularly the systemic immune-inflammation index (SII), in predicting the necessity for surgical intervention following the failure of medical treatment in TOA patients. Methods: A retrospective analysis was conducted on 101 patients diagnosed with TOA at the Ba & gbreve;c & imath;lar Training and Research Hospital's Department of Obstetrics and Gynecology between January 2019 and June 2023. Data collected included demographic details, obstetric history, chronic conditions, clinical history (including intrauterine interventions), and preoperative admission laboratory parameters (CBC, CRP, Neutrophil-to-Lymphocyte Ratio (NLR), and Systemic Immune-Inflammation Index (SII)). Patients were categorized based on treatment outcomes: successful medical treatment versus surgical intervention. A multivariable logistic regression analysis was conducted to assess the predictive value of these markers and to identify independent predictors of medical treatment failure. Results: The surgical group had significantly higher SII, NLR, and CRP levels compared to the medically managed group. An SII cutoff value of 1750 was a significant predictor of medical treatment failure, with an area under the curve (AUC) of 0.749 (95% CI: 0.649-0.850), yielding a sensitivity of 73.2% and specificity of 76.7%. Similarly, NLR demonstrated predictive value with a cut-off value of 4.3, achieving an AUC of 0.694 (95% CI: 0.590-0.798), with 80.5% sensitivity and 58.3% specificity. In the multivariable analysis, SII (OR: 1.002), NLR (OR: 0.706), length of hospital stay (OR: 1.181), and history of curettage (OR: 7.018) were identified as independent predictors of medical treatment failure. Although the mean abscess diameter was larger in the surgical group (64.0 mm vs 57.5 mm), this difference did not reach statistical significance (p=0.079). Conclusion: Systemic inflammatory markers-particularly, the Systemic Immune-Inflammation Index (SII)-appear to be robust, cost-effective, and readily available tools for predicting medical treatment failure in patients with TOA. Predictive performance is enhanced when SII is interpreted in conjunction with NLR and relevant clinical history, especially prior curettage. Integrating these independent predictors into clinical decision-making may facilitate earlier identification of high-risk patients and expedite escalation to surgical intervention, thereby minimizing delays and improving patient outcomes.
Keywords: tubo-ovarian abscess; systemic immune-inflammation index; surgical treatment; inflammatory markers; pelvic inflammatory disease